Duality of B Cell-CXCL13 Axis in Tumor Immunology - Rubio, Angel J.; Porter, Tyrone; Zhong, Xuemei (Frontiers in Immunology, 2020)
Tumor immunity is a rapidly evolving area of research consisting of many possible permutations of immune cell tumor interactions that are dependent upon cell type, tumor type, and stage in tumor progression. At the same time, the majority of cancer immunotherapies have been focused on modulating the T cell-mediated antitumor immune response and have largely ignored the potential utility that B cells possess with respect to tumor immunity. Therefore, this motivated an exploration into the role B cells and their accompanying chemokine, CXCL13, play in tumor immunity across multiple tumor types. Both B cells and CXCL13 possess dualistic impacts on tumor progression and tumor immunity which is furthered detail in this review. Potential tools for better elucidating the mechanisms by which B cells and CXCL13 impact the antitumor immune response are also discussed. In addition, multiples strategies are proposed for modulating the B cell-CXCL13 axis for cancer immunotherapies.